(untitled) (Boletin Médico de Postgrado, 2024)
In order to analyze the cardiovascular risk factors in patients with non-alcoholic fatty liver disease (NAFLD) who attended the Genus health center during the period April-October 2022, a descriptive cross-sectional study was carried out selecting 30 patients who were characterized by an average age of 47.1 ± 13.6 years, where the most affected group was 51-60 years (26.6%) with a predominance of female sex (53.3%). Patients with NASH were classified by abdominal ultrasound, reporting 66.6% grade I steatosis, 30% grade II and 3.3% grade III. Nutritional status by body mass index was overweight (46.6%), obesity I (30%) and normal weight (16.6%). Glutamic oxaloacetic and pyruvic transaminases were reported as normal in 83.3% of the cases. Low, 33.3% moderate and 10% high cardiovascular risk were reported in 56.6% of the cases. When the severity of NAFLD and cardiovascular risk were related, 55% of the patients with steatosis I had low, 30% moderate and 15% high risk. However, 66.6% of patients with steatosis II showed low risk and 33.3% moderate risk. All cases with steatosis III showed moderate risk. In conclusion, the detection of NASH on conventional ultrasound examination should alert clinicians to the likely coexistence of multiple underlying cardiovascular risk factors that should be investigated and treated.